Achieving greater independence from commercial influence in research. (9th March 2021) - Lexchin, Joel; Bero, Lisa A; Davis, Courtney; Gagnon, Marc-Andre
Abstract : As part of The BMJ's campaign for greater independence from commercial influence in the creation and use of evidence, Joel Lexchin and colleagues outline some approaches to minimise bias in clinical trials